An unusual case of Takayasu arteritis presenting as acute myocardial infarction and ischaemic stroke: Takayasu arteritis as infarction and stroke - Manojlovic, Mia; Golubovic, Sonja; Ilic, Tatjana; Samardzic, Filip; Vuckovic, Biljana; Tomic-Naglic, Dragana; Bajkin, Ivana; Pejakovic, Sladjana (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
INTRODUCTION: Takayasu’s arteritis (TA) is well-known yet rare disorder, defined as a chronic large vessel vasculitis mainly involving the aorta and its major branches. We present a complex case of a 51-year-old female patient who first presented with acute myocardial infarction as an initial manifestation of Takayasu arteritis, and later with an acute onset of ischemic stroke.CASE REPORT: We present a case of 51-year-old female patient who was admitted at the Clinic of Nephrology and Clinical Immunology. During hospitalization, a sudden onset of intense chest pain occurred, followed by a development of heart failure to the level of cardiogenic shock. Electrocardiography showed signs of ST-elevated myocardial infarction (STEMI) of the anterior wall, and an increase in cardiospecific enzymes. CT angiography indicated an occlusion of the left ACC, subclavian and axillary arteries as well as a penetrating aortic ulcer localized infrarenal. In the further course of treatment, left-sided weakness of the body was registered. Head CT scan showed an acute ischemic lesion high parietal on the right, as well as a chronic ischemic lesion on the front right. Doppler ultrasonography of carotid and vertebral arteries registered left occlusion, right ACC / ACE stenosis with suspected "macaroni sign". Final diagnosis of Takayasu arteritis was established and corticosteroids were included in the therapy (primarily in pulse doses) with the first pulse of cyclophosphamide of 1000mg.CONCLUSION: This disease should be considered in young female patients who present with chronic inflammation and acute coronary syndrome.